Fabrication of Antireflection Nanodiamond Particle Film by the Spin Coating Deposition Technique - Chii-Ruey Lin; Hong-Ming Chang; Minh-Khoa BenDao; Hsiu Hsien Chiang; Wei-En Chen (International Journal of Photoenergy)
Diamond-based antireflective (AR) coatings were fabricated using a spin coating of diamond suspension at room temperature as nucleation enhancement procedure and microwave plasma enhanced chemical vapour deposition. Various working pressures were used to investigate their effect on the optical characterization of the as-deposited diamond films. Scanning electron microscopy (SEM) and atomic forced microscopy (AFM) were employed to analyze the surface properties of the diamond films. Raman spectra and transmission electron microscopy (TEM) also were used for analysis of the microstructure of the films. The results showed that working pressure had a significant effect on thickness, surface roughness, and wettability of the as-deposited diamond films. Deposited under 35 Torr or working pressure, the film possessed a low surface roughness of 13.8 nm and fine diamond grain sizes of 35 nm. Reflectance measurements of the films also were carried out using UV-Vis spectrometer and revealed a low reflectance value of the diamond films. The achievement demonstrated feasibility of the proposed spin-coating procedure for large scale production and thus opens up a prospect application of diamond film as an AR coating in industrial optoelectronic device.